2004
DOI: 10.1002/mrm.20010
|View full text |Cite
|
Sign up to set email alerts
|

Targeted nanoparticles for quantitative imaging of sparse molecular epitopes with MRI

Abstract: Before molecular imaging with MRI can be applied clinically, certain problems, such as the potential sparseness of molecular epitopes on targeted cell surfaces, and the relative weakness of conventional targeted MR contrast agents, must be overcome. Accordingly, the conditions for diagnostic conspicuity that apply to any paramagnetic MRI contrast agent with known intrinsic relaxivity were examined in this study. A highly potent paramagnetic liquid perfluorocarbon nanoparticle contrast agent (ϳ250 nm diameter, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
212
1
1

Year Published

2005
2005
2013
2013

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 265 publications
(218 citation statements)
references
References 29 publications
4
212
1
1
Order By: Relevance
“…Thus, the imaging capability provided is not from the SPIO intrinsically, but through their influence on longitudinal and transverse relaxation of the surrounding nuclei. Although the ability of SPIO to significantly reduce the spin-spin relaxation (T2) time is generally relied on for generating MR contrast, 68,99 it has also been demonstrated that SPIO can generate sufficient T1 contrast for biomedical applications as well; SPIO possess both high R1 and R2 relaxivities. 118,127 Upon removal of the magnetic field, Brownian motion is sufficient to randomize the SPIO orientations leaving no magnetic remanence.…”
Section: Magnetismmentioning
confidence: 99%
“…Thus, the imaging capability provided is not from the SPIO intrinsically, but through their influence on longitudinal and transverse relaxation of the surrounding nuclei. Although the ability of SPIO to significantly reduce the spin-spin relaxation (T2) time is generally relied on for generating MR contrast, 68,99 it has also been demonstrated that SPIO can generate sufficient T1 contrast for biomedical applications as well; SPIO possess both high R1 and R2 relaxivities. 118,127 Upon removal of the magnetic field, Brownian motion is sufficient to randomize the SPIO orientations leaving no magnetic remanence.…”
Section: Magnetismmentioning
confidence: 99%
“…[8] for ␣ by setting CNR ϭ 5 and performing a numerical fit (R 2 ϭ 0.99) for a realistic range of values (40 Ͻ Ͻ 600), which yields ␣ ϭ Ϫ 10.5 /͑1Ϫ ͒ ϩ 0.642 1/͑1Ϫ ͒ ϩ 0.36. [9] To generalize Eq. [9] for different values of CNR, substitute with NEW ϭ ͑5/CNR NEW ͒ .…”
Section: Theorymentioning
confidence: 99%
“…[9] To generalize Eq. [9] for different values of CNR, substitute with NEW ϭ ͑5/CNR NEW ͒ . Now, we allow Eq.…”
Section: Theorymentioning
confidence: 99%
“…While not unreasonable in theory, the detection limit of a low MW targeted agent has not, to the best of our knowledge, been quantitatively tested in a simple model system. Most studies reporting quantitative detection levels of T 1 agents are based upon binding of a chelate to a soluble protein, total Gd 3+ taken into cells, or Gd 3+ -loaded nanoparticles with an affinity for cells [1,15,22,23]. For example, the limit of detection for simple Gd 3+ -chelates in cells has been reported to range from 10 7 -10 8 Gd 3+ -chelates per cell [15,22] which, for a cell diameter of 5 µm, corresponds to concentrations ranging from 130 µM to 1.3 mM.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the limit of detection for simple Gd 3+ -chelates in cells has been reported to range from 10 7 -10 8 Gd 3+ -chelates per cell [15,22] which, for a cell diameter of 5 µm, corresponds to concentrations ranging from 130 µM to 1.3 mM. Molecular epitopes have been successfully targeted using ~250 nm diameter nanoparticles that contain > 90,000 Gd 3+ chelates/particle [23] although this report did not indicate the concentration of the receptors that could be detected. Although the concentration of the nanoparticles at the estimated detection limit was reported as 113 pM, this corresponds to a Gd 3+ concentration of 10 µM.…”
Section: Introductionmentioning
confidence: 99%